Physical activity, cardiorespiratory fitness and venous thromboembolism - Evensen, Line Holtet (Seminars in Thrombosis and Hemostasis, 2020)
Venous thromboembolism (VTE) is a serious disease that represents a growing public health concern, and identification of modifiable risk factors is a priority. Although physical activity and cardiorespiratory fitness (CRF) are associated with a wealth of health benefits, their associations with VTE remain to be established. The aim of the present thesis was to summarize knowledge and to identify important knowledge gaps. Further, we aimed to study the association between physical activity, CRF and the risk of incident VTE. Finally, we wanted to investigate whether physical activity was associated with risk of recurrence and mortality after VTE. The thesis comprises four papers, and is based on data from the Tromsø study. Participant information was collected via self-administered questionnaires, physical examinations and blood samples. Information on physical activity was collected from the questionnaires, and CRF was estimated from physical activity as well as other physical variables. In Paper I, we concluded that the literature on physical activity and VTE risk was diverging, but suggestive of a beneficial role of physical activity. We proposed that future studies should account for fluctuations in activity during follow-up, explore BMI as a potential mediator and use objective assessment strategies. In Paper II, we reported that physical activity was associated with a lower risk of incident VTE, and that only a small to moderate proportion of the association was mediated by BMI. In Paper III, we found that higher estimated CRF was associated with a lower VTE risk, and these effect sizes were larger than for physical activity. Finally, Paper IV revealed that physical activity was associated with a lower risk of mortality after incident VTE, but did influence recurrence risk. Our results imply that regular physical activity and CRF may comprise modifiable targets for primary prevention of VTE and improved prognosis after VTE.